Atrakcyjność inwestycyjna Polski dla inwestorów japońskich - Kuźmiak, Joanna (The Investment Attractivity of Poland for Japanese Investors, 2008)
In this article, the author attempts to rate the investment attractiveness of Poland for Japanese investors. Coming to a conclusion one may state that the main objective remains the further creation of a positive image of our country and its economy. According to recent studies and the reports of international organisations, the investment attractiveness of Poland is systematically increasing. Japanese entrepreneurs invest in Poland more frequently.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 28, s. 137-146